In vitro Prebiotic Effect of Bread-Making Process in Inflammatory Bowel Disease Microbiome - Lluansí, Aleix; Llirós, Marc; Oliver, Lia; Bahí, Anna; Elias-Masiques, Núria; Gonzalez, Marina; Benejam, Patrícia; Cueva, Emilio; Termes, Miquel; Ramió-Pujol, Sara; Malagón, Marta; Amoedo, Joan; et al. (Frontiers in Microbiology, 2021)
Inflammatory bowel disease (IBD), including its two main categories (Crohn's disease and ulcerative colitis), has been linked both to gut microbiota and to diet. Bread is a daily food that has a potential capacity as a prebiotic. Our aim was to evaluate different bread-making processes and their effect on fecal colonic microbiota in IBD patients. The microbial composition of several sourdoughs and dough samples was analyzed by high-throughput sequencing of 16S and 18S rRNA genes. Three types of bread, which followed different bread-making processes, were in vitro digested and incubated with feces from IBD patients. Changes in gut microbiota were assessed by a quantitative polymerase chain reaction using specific bacterial sequence targets. Short-chain fatty acid production was also analyzed by gas chromatography. Lactobacillus sanfranciscensis was the dominant lactic acid bacteria species found in sourdough and bread doughs prepared using sourdough, whereas Saccharomyces cerevisiae was the most dominant yeast in all groups, especially in bread doughs before baking. Differences in microbial composition in raw bread doughs were more related to the type of dough and elaboration than to fermentation time lengths. The analysis of in vitro fecal incubations with bread conditions revealed an increase in most bacterial groups analyzed and short-chain fatty acid production, both in Crohn's disease and ulcerative colitis samples. Most remarkable increases in short-chain fatty acid production mirrored higher abundances of Roseburia species. The potential prebiotic properties observed were mainly obtained when using a high quantity of bread, regardless of bread type. Overall, this study highlights the bacterial dynamics within the bread-making process and the potential prebiotic effect in IBD patients.